2019
DOI: 10.5204/ssj.v10i3.1275
|View full text |Cite
|
Sign up to set email alerts
|

Belonging as a Resource of Resilience: Psychological Wellbeing of International and Refugee Students in Study Preparation at German Higher Education Institutions

Abstract: After 2015, several German higher education institutions (HEI) expanded their capacities for the study preparation of refugees. Nowadays, international and refugee students prepare for higher education degree programs through languages courses and subject-specific preparation courses at universities and colleges. So far, empirical research on refugee students’ wellbeing, in comparison to international students is scarce. This article elaborates on study preparation at German HEIs and refugee students’ psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…A social approach to resilience shifts from an internal characteristic to something both produced by and acting on social connections. This aligns to Grüttner's (2019) research where wellbeing is enhanced by students' sense of belonging. We can see this in how international students prepare for studying in Australia by building and relying on social networks prior to coming to the university, as well as how they "give back" to others through their academic career.…”
Section: Conclusion: Resilience and Finding Belonging In A Pandemicsupporting
confidence: 84%
See 1 more Smart Citation
“…A social approach to resilience shifts from an internal characteristic to something both produced by and acting on social connections. This aligns to Grüttner's (2019) research where wellbeing is enhanced by students' sense of belonging. We can see this in how international students prepare for studying in Australia by building and relying on social networks prior to coming to the university, as well as how they "give back" to others through their academic career.…”
Section: Conclusion: Resilience and Finding Belonging In A Pandemicsupporting
confidence: 84%
“…This social approach shifts resilience from an internal or individual characteristic to a social quality or a relational capacity. For example, survey research of German international and refugee students in higher education suggests that wellbeing was compromised by social exclusion, whereas feeling a sense of belonging within a course cohort was a source of resilience (Grüttner, 2019). This mirrors research with other population groups, such as studies of medical education students, refugee children, and participants of youth adventure education, where belonging is found to enhance resilience (McKenna et al, 2016;Pieloch et al, 2016;Scarf et al, 2016).…”
Section: Resilience Belonging Connection and International Studentsmentioning
confidence: 99%
“…I will now take the liberty of making one last comment for the current occasion of the Covid-19 pandemic: Prospective refugee students particularly benefit from experiences of social integration, which goes hand in hand with social recognition and appreciation in study preparation programmes (Grüttner, 2019). Existing educational inequalities are likely to be exacerbated in the course of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…There are also some studies on the effects of social belonging with a focus on ethnically diverse student samples. A cross-sectional study on international students and refugees in Germany showed that a sense of belonging to the study preparatory course was positively associated with subjective well-being and buffered the negative effect of xenophobia (Grüttner, 2019). In an intervention study with African-American and white students in their first study year, Hausmann et al (2007) showed that a sense of university belonging predicted the intention to persist beyond other predictors in both groups.…”
Section: A Sense Of University Belonging and Psychological And Academic Adaptationmentioning
confidence: 99%